Veto rights in international joint ventures - Reuer, Jeffrey J.; Klijn, Elko; Devarakonda, Shivaram; Olie, René (Journal of International Business Studies, 2024)
Notwithstanding their popularity, veto rights are inadequately understood features of international agreements, particularly interfirm exchanges such as international joint ventures (IJVs). As an interesting feature of an IJV’s governance design, they shape decision-making of the most powerful administrative mechanism of an IJV – the IJV board. IJVs’ boards play a crucial part in supporting adaptation to contingencies, but their adaptive capacity can also give rise to a different set of concerns, however: their opportunistic use by a partner in control of the board. Such behavior, we argue, can be reined in by veto rights. Building on transaction cost economics, we posit that goal conflicts owing to partner competition and environmental uncertainty contribute to the allocation of veto rights to partners. Concerns surrounding the maladaptive use of board control weaken when institutional safeguards are strong, reducing the need for veto rights. Findings from a survey of IJVs furnish evidence in support of the core proposition that veto rights can help parent firms address maladaptation. We conclude that veto rights can be an important element of partners’ arsenal when designing and governing IJVs based on comparative efficiency considerations.